Pengaruh Insentif dan Komitmen Organisasional terhadap Motivasi Kerja Dosen pada Institut Agama Islam Negeri Kerinci - Yani, Ahmad; Elfiswandi, Elfiswandi; Lusiana, Lusiana; Sari, Silvia (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This This abstract discusses the work motivation of lecturers at the Kerinci State Islamic Institute (IAIN) with a focus on the influence of incentives and commitment on work motivation. This research methodology involves the use of a questionnaire distributed to 70 IAIN Kerinci lecturers to collect primary data. Data collection also involved interviews, library research, and field research. Data analysis includes testing validity and reliability using statistical programs, such as SPSS. The test results show that most of the statements in the questionnaire are valid and reliable for use in this research. Descriptions of respondents based on age, gender, education and marital status are also presented in this abstract. Apart from that, there is an explanation of the results of the data normality test which shows that the incentive, commitment and work motivation variables have a distribution that tends to be normal. In this research, it is explained that there is a significant influence between incentives, commitment and work motivation on.